Estimation of Minimum Biofilm Eradication Concentration (MBEC) on In Vivo Biofilm on Orthopedic Implants in a Rodent Femoral Infection Model - Okae, Yu; Nishitani, Kohei; Sakamoto, Akio; Kawai, Toshiyuki; Tomizawa, Takuya; Saito, Motoo; Kuroda, Yutaka; Matsuda, Shuichi (Frontiers in Cellular and Infection Microbiology, 2022)
The formation of a biofilm on the implant surface is a major cause of intractable implant-associated infection. To investigate the antibiotic concentration needed to eradicate the bacteria inside a biofilm, the minimum biofilm eradication concentration (MBEC) has been used, mostly against in vitro biofilms on plastic surfaces. To produce a more clinically relevant environment, an MBEC assay against biofilms on stainless-steel implants formed in a rat femoral infection model was developed. The rats were implanted with stainless steel screws contaminated by two Staphylococcus aureus strains (UAMS-1; methicillin-sensitive Staphylococcus aureus, USA300LAC; methicillin-resistant Staphylococcus aureus) and euthanized on days 3 and 14. Implants were harvested, washed, and incubated with various concentrations (64–4096 μg/mL) of gentamicin (GM), vancomycin (VCMVA), or cefazolin (CEZCZ) with or without an accompanying systemic treatment dose of VCMVA (20 μg/mL) or rifampicin (RFPRF) (1.5 μg/mL) for 24 h. The implant was vortexed and sonicated, the biofilm was removed, and the implant was re-incubated to determine bacterial recovery. MBEC on the removed biofilm and implant was defined as in vivo MBEC and in vivo implant MBEC, respectively, and the concentrations of 100% and 60% eradication were defined as MBEC100 and MBEC60, respectively. As for in vivo MBEC, MBEC100 of GM was 256–1024 μg/mL, but that of VCMVA and CEZCZ ranged from 2048–4096 μg/mL. Surprisingly, the in vivo implant MBEC was much higher, ranging from 2048 μg/mL to more than 4096 μg/mL. The addition of RFPRF, not VCMVA, as a secondary antibiotic was effective, and MBEC60 of day 3 USA300LAC biofilm was reduced from 1024 μg/mL with GM alone to 128 μg/mL in combination of RFPRF and the MBEC60 on day 14 on USA300LAC biofilm was reduced from 2048 μg/mL in GM alone to 256 μg/mL in combination of RFPRF. In conclusion, a novel MBEC assay for in vivo biofilms on orthopedic implants was developed. GM was the most effective against both methicillin-sensitive and methicillin-resistant Staphylococcus aureus, in in vivo biofilms, and addition of systemic concentration of RFPRF reduced MBEC of GM. Early initiation of treatment is desired because the required concentration of antibiotics increases with biofilm maturation.